Single Nanoparticle Magnetic Spin Memristor. Issue 30 (27th June 2018) - Al‐Bustami, Hammam; Koplovitz, Guy; Primc, Darinka; Yochelis, Shira; Capua, Eyal; Porath, Danny; Naaman, Ron; Paltiel, Yossi
Abstract: There is an increasing demand for the development of a simple Si‐based universal memory device at the nanoscale that operates at high frequencies. Spin‐electronics (spintronics) can, in principle, increase the efficiency of devices and allow them to operate at high frequencies. A primary challenge for reducing the dimensions of spintronic devices is the requirement for high spin currents. To overcome this problem, a new approach is presented that uses helical chiral molecules exhibiting spin‐selective electron transport, which is called the chiral‐induced spin selectivity (CISS) effect. Using the CISS effect, the active memory device is miniaturized for the first time from the micrometer scale to 30 nm in size, and this device presents memristor‐like nonlinear logic operation at low voltages under ambient conditions and room temperature. A single nanoparticle, along with Au contacts and chiral molecules, is sufficient to function as a memory device. A single ferromagnetic nanoplatelet is used as a fixed hard magnet combined with Au contacts in which the gold contacts act as soft magnets due to the adsorbed chiral molecules. Abstract : There is an increasing demand for the development of a simple Si‐based universal memory device at the nanoscale. In this paper; a simple, low voltage, memristor‐like, universal spintronic magnetic memory device at 30 nm size, is presented. The device is Si‐compatible and operates under ambient conditions. The simplicity of the device is accomplished by applying the chiral‐induced spin selectivity effect.